A Globally Conforming Lattice Structure for 2D Stress Tensor Visualization. (18th July 2020) - Wang, Junpeng; Wu, Jun; Westermann, Rüdiger
Abstract: We present a visualization technique for 2D stress tensor fields based on the construction of a globally conforming lattice. Conformity ensures that the lattice edges follow the principal stress directions and the aspect ratio of lattice elements represents the stress anisotropy. Since such a lattice structure cannot be space‐filling in general, it is constructed from multiple intersecting lattice beams. Conformity at beam intersections is ensured via a constrained optimization problem, by computing the aspect ratio of elements at intersections so that their edges meet when continued along the principal stress lines. In combination with a coloring scheme that encodes relative stress magnitudes, a global visualization is achieved. By introducing additional constraints on the positional variation of the beam intersections, coherent visualizations are achieved when external loads or material parameters are changed. In a number of experiments using non‐trivial scenarios, we demonstrate the capability of the proposed visualization technique to show the global and local structure of a given stress field.